WHY ENERGY ACCESS IS NOT ENOUGH FOR CHOOSING CLEAN COOKING FUELS? EVIDENCE FROM THE MULTINOMIAL LOGIT MODEL - Kapsalyamova, Zhanna; Mishra, Ranjeeta; Kerimray, Aiymgul; Karymshakov, Kamalbek; Azhgaliyeva, Dina (Academic Press, 2021)
The transition to sustainable energy requires an assessment of drivers of the use of clean and dirty fuels for cooking. Literature highlights the importance of access to clean fuel for switching from dirty fuels to clean fuels. Though access to cleaner fuels, such as electricity promotes clean fuel use, it does not necessarily lead to a complete transition to the use of clean fuels. Households continue using traditional fuels in addition to the clean fuels. The main objective of this paper is to explain the choice of dirty cooking fuels even when access to electricity is provided. We use nationally representative household survey data to study the household energy use decisions in three middle-income countries, namely, India, Kazakhstan, and the Kyrgyz Republic. The study discusses the role of access to natural gas, free fuel, convenience or multi-use of fuels featured by the heating system installed, built-in environment, and other socio-economic factors in household fuel choice for cooking. The results show that access to natural gas increases the likelihood of opting for clean fuel, while the availability of free fuel in rural areas and the coal-based heating system promote the use of solid fuels.
Keywords: Type of access: Open Access; Cooking fuel; Energy access; Fuel choices; Multiple fuel use